Enteritis infecciosa de los terneros I. Estudio de tres brotes en diferentes localidades del país - Arroyo, Guido (1959)
Three outbreaks of calf enteritis were investigated. Salmonella typhi-murium was isolated from two of them, and a Salmonella of group E 1 from the third. In no instance was S. dublin found; pending further investigation, therefore, the suggestion is made that calves and pregnant cows should be immunized with vaccine prepared from the isolates of each outbreak, as commercial or other vaccines prepared from S. dublin are likely to be of little value